Growth potential of Grass Carp, Ctenopharyngodon idella, Val. in Saline water with an Aquatic weed Potamogeton pectinatus as feed - Routray, Padmanav; M.D., Routray (Fishery Technology, 2025)
The Growth potential of farmed grass carp, Ctenopharyngodon idella were studied at seven different salinities (3-9). The Chinese strain grass carp was selected as production reference. The result showed a significant growth rate (p < 0.01) upto 6 ppt saliniity. At lower salinities the consumption of brackishtwater weed potamogeton pectinatus was found to be high thereby accilerating the growth. The result also suggests that the growth potential of grass carp has generally been underestimated at salinities upto 7 ppt Therefore, small scale production of grass carp is feasible in low saline areas particularly the salinity affected agricultural areas